Stages of Biological Development across Age: An Analysis of Canadian Health Measure Survey 2007–2011 - Chao, Yi-Sheng; Wu, Hsing-Chien; Wu, Chao-Jung; Chen, Wei-Chih (Frontiers in Public Health, 2018)
Introduction The stages of biological development are not clearly defined despite the fact that they have been used to refer to concepts such as adolescence and aging. This study aimed to 1) test whether stages can be defined, 2) identify stages of representative components, 3) and attempt to interpret the representative components in a health and biomarker database. Methods This study analyzed the data on the Canadian Health Measures Survey (CHMS) interviewees from cycle one to three (2007 to 2013) in Canada. We selected 282 biomarkers and related features after redundant variables were removed with correlation. Fifty-nine categorical variables were replaced by 122 binominal variables, leaving 345 variables for analysis. Principal component (PC) analysis was conducted to summarize the data and the loadings were used to interpret the PCs. A stable stage was assumed to be the age groups without significantly different values of principal components (PCs). Results The CHMS interviewed 16340 Canadians. Of all, 51.25% were female. The age ranged from 6 to 79 years (mean=34.41 years, 95% CI= 34.74 to 34.08). The proportions of total variance explained by the first three PCs were 12.14%, 4.03% and 3.19% respectively. The differences of the first PC were not significant, especially between age 22 and 33 years, 34 and 40, 41 and 45, 46 and 71, and 72 and 79 (adjusted p > 0.05 for all). Discussion and Conclusions There are stages of stability and transition across all age groups based on the first PCs. The first and second PCs are related to physical development and lung function. There are stages of stability and transition identified. The identification of stable stages is the first step to understanding how human biology develops in a population perspective and will be important for research that relies on a research population with similar characteristics to draw samples for observation or intervention.